(untitled) (mathematica didactica, 2022)
This paper describes an approach to how formal mathematics can be applied to empirical objects. Since, on the one hand, mathematics should be experienced in the classroom as an intellectual creation of its own kind, but, on the other hand, it is often applied to the reality surrounding us or practiced on empirical objects, the challenges should be addressed in mathematics educational research. In physics, thinking about the application of formal mathematics to reality has a long tradition. This article applies a concept for the application of mathematics to reality from theoretical physics - the methodology of Günther Ludwig - to school geometry in order to provide didactic suggestions on the relationship between mathematics and reality.